2022
DOI: 10.1021/acs.joc.2c01956
|View full text |Cite
|
Sign up to set email alerts
|

Acetyl Group Migration in Xylan and Glucan Model Compounds as Studied by Experimental and Computational Methods

Abstract: It was recently demonstrated by us that acetyl groups in oligosaccharides can migrate not only within one saccharide unit but also between two different saccharide units. Kinetics of this phenomenon were previously investigated in both mannan model compounds and a naturally occurring polysaccharide. In addition to mannans, there are also several other naturally acetylated polysaccharides, such as xyloglucans and xylans. Both xyloglucans and xylans are some of the most common acetylated polysaccharides in natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The same mechanism was applied to acetyl group migration over the glycosidic bond in both glycan and mannan trisaccharides, with good results considering the challenge of calculating the pK a s and the conformations of such flexible trisaccharides. [17] The mechanism in aqueous media differs from those in other solvents, where the possibility for migration under acidic or neutral conditions becomes more viable. One such example was studied by Crout and co-workers.…”
Section: The Mechanismmentioning
confidence: 99%
See 4 more Smart Citations
“…The same mechanism was applied to acetyl group migration over the glycosidic bond in both glycan and mannan trisaccharides, with good results considering the challenge of calculating the pK a s and the conformations of such flexible trisaccharides. [17] The mechanism in aqueous media differs from those in other solvents, where the possibility for migration under acidic or neutral conditions becomes more viable. One such example was studied by Crout and co-workers.…”
Section: The Mechanismmentioning
confidence: 99%
“…Most of the earlier studies on acyl group migration have been performed in monosaccharides [2] . Recently, however, also investigations on acyl group migration in oligo‐ and polysaccharides have been reported [17,22] . These studies have demonstrated that an acetyl group may also migrate across the glycosidic linkage, from a secondary to a primary hydroxyl group in both oligosaccharides (Scheme 2) and a native polysaccharide.…”
Section: The Migrationmentioning
confidence: 99%
See 3 more Smart Citations